Sensitivity Analysis of the Surface Acoustic Wave Sensor towards Size-Distributed Particulate Matter - Jian Yang; Jianan Lu; Shanmeng Zhang; Dong Guan (Shock and Vibration)
To study the sensitivity of the surface acoustic wave (SAW) sensor towards particulate matter (PM), an analytic model has been built based on single particle perturbation theory of full size range and the lognormal size distribution of the PM. The sensitivity of the frequency shift to 1 nanogram of PM has been calculated. The model shows that the frequency shift is a result of the competition between the negative perturbation by mass loading and the positive perturbation by elastic coupling, determined by particle size distribution parameters, material, and SAW frequency. To verify the model, the relationship of the frequency shift of a 315 MHz SAW to the concentration of aerosols generated by two kinds of powders of different sizes was measured. The experiment is in agreement with the model: the sensor has shown negative sensitivity towards aerosols generated by the finer particles of 1 μm, 3 μm polytetrafluoroethylene (PTFE), and A1 Arizona dust and positive sensitivity towards aerosols generated by the coarser particles of 10 μm PTFE and A4 Arizona dust; and the negative sensitivity is about 1 order higher than the positive.